A copper/O2-mediated direct sp3 C–H/N–H cross-dehydrogen coupling reaction of acylated amines and N-aryl glycine esters. Issue 16 (4th April 2018) - Sun, Bin; Wang, Yao; Li, Deyu; Jin, Can; Su, Weike
Abstract : We described a mild and efficient CDC reaction between N -aryl glycine esters and various acylated amines for the synthesis of α-amino α-amide acid esters with an excellent regioselectivity in the presence of copper salts. Abstract : A copper salt-catalyzed cross-dehydrogenative coupling reaction between N -aryl glycine esters and acylated amines has been developed. The reaction proceeded effectively under an oxygen atmosphere without the use of peroxide agents. This simple protocol allows for the preparation of a series of new compounds in a moderate to excellent yield via the CDC reaction of a wide range of N -aryl glycine derivatives with acylated amines, which are of great interest in the field of medicinal chemistry. A plausible mechanism involving the formation of an iminium ion intermediate, followed by coupling with acylated amines was proposed after some control experiments were conducted.